2010
DOI: 10.5146/tjpath.2010.01017
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant fibrous histiocytoma of the kidney: report of a case

Abstract: Primary renal malignant fibrous histiocytoma is extremely rare. The prognosis is generally poor because of the high rate of local recurrence even if radical surgery is performed. We report a case of primary renal malignant fibrous histiocytoma in a 43-year-old woman. A well-defined renal mass (10x9x7cm) with lobulated contour was revealed by abdominal ultrasonography and computerized tomography in our patient who presented with left-flank pain. The contralateral kidney and renal functions were normal. No other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(7 reference statements)
1
1
0
Order By: Relevance
“…The malignant fibrous histiocytomas has a nodular, multinodular and firm macroscopic appearance. Cut surfaces of tumors has non specific appearance such as necrosis, not encapsulated and with pale white color (Datarkar and Hazare, 2009;Kiran et al, 2005;Turk, 2010). The macroscopic findings determined in this case study were found to be in parallel with those reported in previous case studies.…”
Section: Discussionsupporting
confidence: 80%
“…The malignant fibrous histiocytomas has a nodular, multinodular and firm macroscopic appearance. Cut surfaces of tumors has non specific appearance such as necrosis, not encapsulated and with pale white color (Datarkar and Hazare, 2009;Kiran et al, 2005;Turk, 2010). The macroscopic findings determined in this case study were found to be in parallel with those reported in previous case studies.…”
Section: Discussionsupporting
confidence: 80%
“…3,4 Some cases in the kidneys, prostate, urinary bladder, spermatic cord, liver, pancreas, thyroid and breast were rarely reported. 2,[5][6][7][8][9][10][11] There are 4 defined histomorphological patterns of MFH: (1) storiform-pleomorphic subtype, (2) myxoid subtype, (3) giant cell subtype and (4) inflammatory subtype (in order of frequency). Giant cell subtypes are lesions consisting of widespread hemorrhagic and necrotic areas histologically characterized by numerous multinuclear osteoclast-type giant cells.…”
Section: Introductionmentioning
confidence: 99%